2018
DOI: 10.1021/acs.jpcc.8b03075
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable and Flexible Resistive Memory for Transient Electronics

Abstract: Physically transient electronics have attracted increasing attention recently due to their potential as the basis for building “green” electronics and biomedical devices. In the development of transient devices for biomedical applications, however, the dilemma between the strictly required biodegradability and device performance has brought great difficulties to the material selection. In this paper, we introduced silk fibroin as dielectric layer to fabricate biodegradable resistive memory devices. Comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…While a number of transient memory devices were reported that dissolve in water-a recent review is given here, [101] -only a few of them are completely biodegradable, leaving nontoxic residues. Ji and co-workers realized a biodegradable metal-insulator-metal device, using W and Mg as electrodes (80 nm each) and silk fibroin (120 nm) as switching layer [131] (Figure 6h). The silk fibroin film was obtained from a silk cocoon and prepared in a three-step process that includes boiling, dissolving, and spinning.…”
Section: Switching: Transistors and Memorymentioning
confidence: 99%
“…While a number of transient memory devices were reported that dissolve in water-a recent review is given here, [101] -only a few of them are completely biodegradable, leaving nontoxic residues. Ji and co-workers realized a biodegradable metal-insulator-metal device, using W and Mg as electrodes (80 nm each) and silk fibroin (120 nm) as switching layer [131] (Figure 6h). The silk fibroin film was obtained from a silk cocoon and prepared in a three-step process that includes boiling, dissolving, and spinning.…”
Section: Switching: Transistors and Memorymentioning
confidence: 99%
“…However no systematic investigations of PPS‐based ion exchange and chemical adsorption resin have been reported besides the synthesis of fibrous ion exchanger in our lab since 2012 . The small molecule reagents that modified the PPS resin in this paper are cheap and easy to obtain; moreover, the reagents contain N, S atoms, which can form coordination with heavy metal ions . The reaction is simple, which do not need catalyst, high temperature, and high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–10 ] These drawbacks have limited the applications of protein‐based implantable synapse devices. [ 8–12 ] The macroscopic performance of protein materials is determined by the inner structure. [ 13–16 ] Therefore, optimizing the basic structure of protein materials to make them more stable and controllable is a key approach to fabricate out‐standing device performance.…”
Section: Introductionmentioning
confidence: 99%